Reaching out to the academe a study on the reference services of academic archives in Metro Manila - Mariano, Randolf D. (2010)
In the Philippines, university libraries and museums have already proven their educational missions and core functions. Both have designed dynamic reference activities and educational outreach components to fulfill their respective missions. However, archivists are still addressing the need to improve reference services in academic archives.